The relationship between low birthweight and socioeconomic status in Ireland - David Madden (University College Dublin, UCD School of Economics, 2012)
There is now fairly substantial evidence of a socioeconomic gradient in low birthweight for developed countries. The standard summary statistic for this gradient is the concentration index. Using data from the recently published Growing Up in Ireland survey, this paper calculates this index for low birthweight arising from preterm and intrauterine-growth-retardation. It also carries out a decomposition of this index for the different sources of low birthweight and finds that income inequality appears to be less important for the case of preterm births, while fathers education and local environmental conditions appear to be more relevant for IUGR. The application of the standard Blinder-Oaxaca decomposition also indicates that the socioeconomic gradient for all sources of birthweight appear to arise owing to different characteristics of rich and poor, and not because the return to characteristics differ between rich and poor.
Keywords: I10; I14; 330; Low birthweight; Concentration Index; decomposition